Informing Alcohol Interventions for Student Service Members/Veterans: Normative Perceptions and Coping Strategies - Miller, Mary Beth (Addict Behav, 2016)
OBJECTIVE: The current study aimed to inform future interventions for heavy alcohol use and problems among college students by examining the utility of normative perceptions and coping strategies in predicting alcohol use among student service members/Veterans (SSM/Vs). METHODS: SSM/Vs and civilian students (N = 319) at a large university in the Southern Plains completed self-report measures of demographics, alcohol use and related behaviors, and coping strategies. RESULTS: Both SSM/Vs and civilian students significantly overestimated the typical weekly drinking quantities and frequencies of same-sex students on campus. Among SSM/Vs, normative perceptions of typical student (not military-specific) drinking and substance-related coping strategies significantly predicted drinks consumed per week, while substance-related coping predicted alcohol-related consequences. CONCLUSIONS: Despite the theoretical importance of similarity to normative referents, military-specific norms did not significantly improve the prediction of SSM/Vs’ personal drinking behavior. Moreover, neither typical student nor military-specific norms predicted alcohol-related consequences among SSM/Vs after accounting for substance-related coping strategies. Future research may examine the efficacy of descriptive normative feedback and the importance of military-specific norms in alcohol interventions for SSM/Vs.